The Efficiency of Secondary Schools in an International Perspective Preliminary Results from PISA 2012 - Agasisti, Tommaso (OECD Education Working Papers, 2015)
As governments around the world struggle with doing more with less, efficiency analysis climbs to the top of the policy agenda. This paper derives efficiency measures for more than 8,600 schools in 30 countries, using PISA 2012 data and a bootstrap version of Data Envelopment Analysis as a method. We estimate that given current levels of inputs it would be possible to increase achievement by as much as 27% if schools improved the way they use these resources and realised efficiency gains. We find that efficiency scores vary considerably both between and within countries. Subsequently, through a second-stage regression, a number of school-level factors are found to be correlated with efficiency scores, and indicate potential directions for improving educational results. We find that many efficiency-enhancing factors vary across countries, but our analysis suggests that targeting the proportion of students below low proficiency levels and putting attention to students' good attitudes (for instance, lower truancy), as well as having better quality of resources (i.e. teachers and educational facilities), foster better results in most contexts